A prevalent alpha-proteobacterium Paracoccus sp. in a population of the Cayenne ticks (Amblyomma cajennense) from Rio de Janeiro, Brazil - Erik Machado-Ferreira; Joseph Piesman; Nordin S Zeidner; Carlos A.G Soares (Genetics and Molecular Biology, 2012)
As Rocky Mountain Spotted Fever is the most common tick-borne disease in South America, the presence of Rickettsia sp. in Amblyomma ticks is a possible indication of its endemicity in certain geographic regions. In the present work, bacterial DNA sequences related to Rickettsia amblyommii genes in A. dubitatum ticks, collected in the Brazilian state of Mato Grosso, were discovered. Simultaneously, Paracoccus sp. was detected in aproximately 77% of A. cajennense specimens collected in Rio de Janeiro, Brazil. This is the first report of Paracoccus sp. infection in a specific tick population, and raises the possibility of these bacteria being maintained and/or transmitted by ticks. Whether Paracoccus sp. represents another group of pathogenic Rhodobacteraceae or simply plays a role in A. cajennense physiology, is unknown. The data also demonstrate that the rickettsial 16S rRNA specific primers used forRickettsia spp. screening can also detect Paracoccus alpha-proteobacteria infection in biological samples. Hence, a PCRRFLP strategy is presented to distinguish between these two groups of bacteria.